Psychiatric comorbidities of attention deficit/hyperactivity disorder in Japan: a nationwide population-based study - Okada, Takashi; Sotodate, Takuma; Ogasawara-Shimizu, Mari; Nishigaki, Nobuhiro (Frontiers in Psychiatry, 2024)
Introduction: This study aimed to estimate prevalence and incidence of attention deficit/hyperactivity disorder (ADHD) and comorbid relationships between ADHD and other psychiatric disorders in Japan. Methods: Using the real-world JMDC Claims Database, we conducted a cross-sectional study (analysis years 2017-2021) and retrospective cohort study (observation 2 years before/after the initial ADHD diagnosis; data collection 2005-2021; enrollment 2017-2019). Patients were male or female, aged 0-57 years. Cross-sectional study patients had an ADHD or other psychiatric disorder diagnosis (with or without medication) and were continuously registered in each analysis year; retrospective study patients had an ADHD diagnosis and ≥2 years' observation before and after diagnosis. Endpoints were annual prevalence and incidence of ADHD in Japan, prevalence and risk ratios of each psychiatric comorbidity in patients with ADHD, prevalence and risk ratios of ADHD in patients with each psychiatric comorbidity, and prevalence of psychiatric disorders before/after the initial ADHD diagnosis. Results: ADHD prevalence in children/adolescents and adults increased each year from 2017 to 2021. Prevalence in boys was 3.5-4.1 times higher than in girls. Prevalence in adults was lower than in children/adolescents, with a small sex difference. ADHD was highly comorbid with various psychiatric disorders. In 2019, the most common comorbidity in children/adolescents with ADHD was autism spectrum disorder (ASD; 54.4%); in adults, it was mood disorders (60.9%). ADHD prevalence in patients with various psychiatric disorders was higher than in the control population. ADHD prevalence was highest in patients with oppositional defiance disorder among both children/adolescents and adults (77.2% and 69.2%, respectively). In the retrospective cohort study (N = 14,940), the most common psychiatric disorders diagnosed prior to ADHD diagnosis were ASD in children/adolescents (33.9% of patients), and mood disorders and sleep disorders in adults (36.9% and 23.8% of patients, respectively). Discussion: ADHD was comorbid with various psychiatric disorders in Japan. In children and adolescents with ADHD, ASD was often diagnosed prior to ADHD. Psychiatric disorders, especially mood disorders and sleep disorders, were frequently diagnosed prior to the initial ADHD diagnosis in adults. The likelihood of comorbid ADHD should be considered when diagnosing adult patients with psychiatric disorders.